Desenvolvimento florestal, deposição de serapilheira e suas influências em sistemas IPF - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Faced with a reality of population growth and increased demand for food, produced sustainably, integrated systems present themselves in a positive way, promoting the production of various products within their components in synergism, environmentally benefiting the soil and the environment, economically, improving income and socially inducing a more conscious use of resources. Within the integrated systems used, iLP manages the forestry and animal components in consortiums, with great importance being to ensure that one component does not compromise the productivity of another. The forest component influences the system in several ways, shading, litter deposition, soil quality, among others. And the animal component in the same way, with adequate and wellmanaged forage, influences the trampling of animals, incorporation of waste and an increase in resources. Thus, the aim of this work was to evaluate the development of the forestry component, forage component and litter deposition of the iLP system. The experiment is installed at the School Farm of the State University of Goiás, Campus São Luís dos Montes Belos, GO. Three forest species are being studied (Corymbia citriodora, Eucalyptus urophyla and Eucalyptus cloeziana), in two arrangements (single lines and triple lines) and three spacings (1, 2 and 3 meters between trees). The forage spacing is 15 m. Between the lines of the triple arrangement there is a spacing of 3 meters. In the forestry component, the following will be evaluated: I) plant height (cm), II) diameter at breast height (DBH) both data collected at the end of the dry period and at the end of the rainy period and III) monthly litter deposition, quantified by Through the installation of four collectors of 0.25 m2 per plot and arranged along the tree line and in the projection of the canopy of each forest species, the material will be grouped by season (spring, summer, autumn and winter). And for forage, the following will be evaluated: I) height (cm), II) tillers (und), III) dry matter (gm) and IV) green matter (gm). The LSD test at 5% probability will be used to compare the means using the Sisvar 5.6 software. Despite the simultaneous development of components, it is important to conduct the system appropriately so that one does not overlap with another, compromising its productivity. However, integrated systems are presenting themselves as better than conventional and successive planting systems in the same area, in addition to optimizing productive areas, it guarantees the diversification of the environment and income, and the sustainability of production.
Forest development, litter deposition and their influences on IPF systems
Keywords: Silvipastoril; Sistemas Integrados; Ciclagem de nutrientes; Sustentabilidade; Integrated systems; Nutrient cycling; Silvopastoral; Sustainability; CIENCIAS AGRARIAS